Efficacy and safety of netakimab, a novel anti-IL-17 monoclonal antibody, in patients with moderate to severe plaque psoriasis. Results of a 54-week randomized double-blind placebo-controlled PLANETA clinical trial - Luis Puig; Andrey L. Bakulev; Muza M. Kokhan; Alexey V. Samtsov; Vladislav R. Khairutdinov; Maria A. Morozova; Nikita A. Zolkin; Ivan V. Kuryshev; Alexey N. Petrov; Antonina V. Artemeva; Arina V. Zinkina-Orikhan (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Netakimab (NTK), an original humanized anti-interleukin-17 monoclonal antibody, showed therapeutic efficacy in moderate to severe plaque psoriasis in a phase 2 clinical study. Herein we report the results of 54 weeks of a phase 3 trial. Aim. To evaluate the efficacy and safety of two NTK regimens vs. placebo in moderate to severe plaque psoriasis. Methods. PLANETA is the ongoing randomized double-blind placebo-controlled clinical trial. 213 patients with moderate to severe plaque psoriasis were randomly assigned to receive NTK 120 mg once every 2 weeks (NTK Q2W), NTK 120 mg once every 4 weeks (NTK Q4W) or placebo. During the first 3 weeks, patients received subcutaneous injections of NTK or placebo (according to the allocation) once a week. Patients in the NTK Q2W group then received NTK at weeks 4, 6, 8, and 10. Subjects in the NTK Q4W group received NTK at weeks 6 and 10 and placebo at weeks 4 and 8. Patients in the placebo group received placebo injections at weeks 4, 6, 8, and 10. Treatment was unblinded at week 12. During the open-label phase, patients in both NTK groups continued to receive NTK Q4W. The primary efficacy endpoint was the proportion of patients in each group who achieved a 75% or greater reduction from baseline in psoriasis area and severity index (PASI 75) at week 12. Results. A total of 77.7%, 83.3%, and 0% of patients had a PASI 75 response at week 12 in the NTK Q2W, NTK Q4W, and placebo groups, respectively (P 0.0001, Fishers exact test, ITT). The effect was maintained throughout the 1-year treatment. NTK showed a good safety profile and low immunogenicity. Conclusion. Treatment with NTK results in high rates of sustained clinical response in patients with moderate to severe plaque psoriasis. The study is ongoing; thus, long-term use efficacy and safety data are forthcoming.